THE USE OF US' INDEX THEORY TO ENHANCE QUALITY OF LOAN WITHIN BANKING INDUSTRY AND FINANCIAL INSTITUTIONS CASE STUDY: BANK ABC - Uke Marius Siahaan (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2020)
ABSTRACTThe economic crisis has been decreased the performance of Banking Industry in Indonesiaas reflected in the decreasing of Loan Growth and the increasing of Non-Performing Loans (NPLs)ratio since 2015. Increasing NPLs was followed by increasing cost of loan and decreasing ROA ofBanks and others financial institutions therefore Bank should be innovate to enhance its loanquality.This study was conducted to determine influence of leverage towards profitability ratios of68 companies which are debtors of Bank ABC in Performing Loan quality within two groups of US'Index value and tested by Correlation and Linear Regression Analysis. Based on the research’soutputs, it was concluded that in group of US’ Index < 1 leverage has been influencing negativelyto its profitability while on another group, with US’ Index > 1, leverage has been influencingpositively. Those conclusions were reinforced by the decline trend of US 'Index value on financialperformances of 21 debtors were included in the category of watch-list debtors as well as provenin the study case of debtor which is now included into the category of non-performing loans. Thisstudy has shown that US’ Index theory could be implemented in all stages of loan process, such asto analysis the repayment capacity of applicants at the front end, as loan monitoring system atthe middle end, and as a guidance in loan restructuring and collecting repayment at the back endstage. Therefore, this study suggests the use of US’ Index theory as a credit risk control strategyto reducing NPLs in Banks and Financial Institutions in order to enhance its loan quality andgenerate sustainable profit.Key words: NPLs, Cost of Loan, US’ Index, Capital Structure, Linear Regression.